Genetic differentiation of Mexican Holstein cattle and its relationship with Canadian and U.S. Holsteins - García-Ruiz, Adriana; Ruiz-López, Felipe de J.; Van Tassell, Curtis P.; Montaldo, Hugo H.; Huson, Heather J. (Frontiers in Genetics, 2015)
The Mexican Holstein industry has imported Canadian and US (CAN+USA) Holstein germplasm for use in two different production systems, the conventional (Conv) and the low income system (Lowi). The objective of this work was to study the genetic composition and differentiation of the Mexican Holstein cattle, considering the production system in which they perform and their relationship with the Canadian and US Holstein populations. The analysis included information from 149, 303 and 173 unrelated or with unknown pedigree Holstein (HO) animals from the Conv, Lowi and CAN+USA populations, respectively. Canadian and US Jersey (JE) and Brown Swiss (BS) genotypes (162 and 86, respectively) were used to determine if Mexican Holsteins were hybridized with either of these breeds. After quality control filtering, a total of 6,617 out of 6,836 SNP markers were used. To describe the genetic diversity across the populations, principal component (PC), admixture composition, and linkage disequilibrium (r2) analyses were performed. Through the PC analysis, HOxJE and HOxBS crossbreeding was detected in the Lowi system. The Conv system appeared to be in between Lowi and CAN+USA populations. Admixture analysis differentiated between the genetic composition of the Conv and Lowi systems, and five ancestry groups associated to sire’s country of origin were identified. The minimum distance between markers to estimate a useful LD was found to be 54.5 kb for the Mexican HO populations. At this average distance, the persistence of phase across autosomes of Conv and Lowi systems was 0.94, for Conv and CAN+USA was 0.92 and for the Lowi and CAN+USA was 0.91. Results supported the flow of germplasm among populations being Conv a source for Lowi, and dependent on migration from CAN+USA. Mexican Holstein cattle in Conv and Lowi populations share common ancestry with CAN+USA but have different genetic signatures.